Removal of foreign bodies in children's airways using flexible bronchoscopic CO2 cryotherapy. Issue 9 (11th March 2016) - Zhang, Lei; Yin, Yong; Zhang, Jing; Zhang, Hao
Summary: Background: The present retrospective study investigated the safety and efficacy of removing foreign bodies from children's airways using flexible bronchoscopic CO2 cryotherapy instead of traditional foreign body aspiration. Methods: Between October 2012 and June 2014 in the Shanghai Children's Medical Center, we performed flexible bronchoscopic CO2 cryotherapy to remove foreign bodies from the airways of 12 children who ranged in age from 10 to 40 months and analyzed outcomes and complications. Results: Using cryotherapy, we successfully and without complications removed the foreign bodies in eight of 12 children. In two cases, the foreign bodies were removed successfully, but cryotherapy partially damaged the airway mucosa, which caused partial airway obstruction because of the newly developed granulation tissue. We incompletely removed the foreign body in one case and failed to remove the foreign body in another case. No serious adverse reactions or complications were observed after the treatments. Conclusion: Removal of foreign bodies from children's airways using flexible bronchoscopic CO2 cryotherapy may be a safe, easy, and effective method.Pediatr Pulmonol. 2016; 51:943–949 . © 2016 Wiley Periodicals, Inc.